Designing Electronic Structures of Multiscale Helical Converters for Tailored Ultrabroad Electromagnetic Absorption - Feng, Zhaobo; Liu, Chongbo; Li, Xin; Luo, Guangsheng; Zhai, Naixin; Hu, Ruizhe; Lin, Jing; Peng, Jinbin; Peng, Yuhui; Che, Renchao (Nano-Micro Letters, 2024)
Atomic-scale doping strategies and structure design play pivotal roles in tailoring the electronic structure and physicochemical property of electromagnetic wave absorption (EMWA) materials. However, the relationship between configuration and electromagnetic (EM) loss mechanism has remained elusive. Herein, drawing inspiration from the DNA transcription process, we report the successful synthesis of novel in situ Mn/N co-doped helical carbon nanotubes with ultrabroad EMWA capability. Theoretical calculation and EM simulation confirm that the orbital coupling and spin polarization of the Mn–N4–C configuration, along with cross polarization generated by the helical structure, endow the helical converters with enhanced EM loss. As a result, HMC-8 demonstrates outstanding EMWA performance, achieving a minimum reflection loss of −63.13 dB at an ultralow thickness of 1.29 mm. Through precise tuning of the graphite domain size, HMC-7 achieves an effective absorption bandwidth (EAB) of 6.08 GHz at 2.02 mm thickness. Furthermore, constructing macroscale gradient metamaterials enables an ultrabroadband EAB of 12.16 GHz at a thickness of only 5.00 mm, with the maximum radar cross section reduction value reaching 36.4 dB m2. This innovative approach not only advances the understanding of metal–nonmetal co-doping but also realizes broadband EMWA, thus contributing to the development of EMWA mechanisms and applications. Highlights: 1 The energy conversion mechanism is thoroughly analyzed, with a detailed quantitative characterization of the dissipation capacities of polarization, conduction, and magnetic loss. 2 Inspired by DNA transcription, atom and geometry configurations co-modulating multi-scale helical converters achieve the RLmin of −63.13 dB at 1.29 mm, and the maximum RCS reduction value reach 36.4 dB m2. 3 Orbital coupling, spin and cross polarization synergize to realize a 6.08 GHz EAB, further expanding to ultrabroad electromagnetic wave absorption of 12.16 GHz through metamaterial design.